Neurolysis for Treatment of Infraorbital Neuropathy - Ahmet Mahli; Demet Coskun (Case Reports in Medicine)
Two patients, a woman aged 34 and a man aged 56, were included in the study. They reported the existence of pain in the areas of the infraorbital nerve, which, over the last four to five years, aggravated by the stimuli of eating, laughing, and being touched. 2 ml of 0.5% lidocaine was administered to these patients six times percutaneously. It was observed that the ease of pain lasted until the local anesthesia lost its effect, and the pain resumed its original intensity. Neurolysis with 0.5 ml of 50% ethanol was applied to the infraorbital nerve. This procedure was applied to the first patient twice and three times to the second. Thereafter, the patients were cured completely. For the treatment of idiopathic chronic infraorbital neuropathy, the neurolysis of the infraorbital nerve using 50% ethanol could be considered as an effective treatment alternative.